2009
DOI: 10.4314/gmj.v42i2.43601
|View full text |Cite
|
Sign up to set email alerts
|

Rudimentary horn pregnancy: Pre-rupture diagnosis and management

Abstract: SUMMARYRudimentary horn pregnancy is a rare obstetric entity and the diagnosis and management may pose some problems especially in a low-resource center. We report our experience in diagnosing and managing a case of fetal death in a rudimentary horn.Keywords: rudimentary horn, pre-rupture, pregnancy, tourniquet CASE REPORTMadam CA was a 28 years old gravida 6 para 5. She presented to Korle Bu Teaching hospital with a complaint of vaginal bleeding of two days duration. She did not remember the exact date of her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 4 publications
0
52
0
Order By: Relevance
“…The incidence in the general population is estimated to be 4.3%. 1 A unicornuate uterus with a rudimentary horn is the rarest anomaly and results from the failure of one of the Müllerian ducts to develop completely and an incomplete fusion with the contralateral side. 2 The incidence of this anomaly is approximately 0.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence in the general population is estimated to be 4.3%. 1 A unicornuate uterus with a rudimentary horn is the rarest anomaly and results from the failure of one of the Müllerian ducts to develop completely and an incomplete fusion with the contralateral side. 2 The incidence of this anomaly is approximately 0.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of USG as a late gestation diagnostic tool is 26 % [8,9]. MRI appeared to be the ''gold standard'' for diagnosing and grouping utzerine anomalies because of its 98-100 % accuracy [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…In about 84 % of these cases, a contralateral rudimentary horn exists, almost always of a non-communicating type [1,5]. The attachment of the rudimentary horn may vary from a fibromuscular band (separated variety) to an extensive fusion between the two horns where there is no external separation between them [4,6]. This was a case with an extensive fusion between the two horns.…”
Section: Introductionmentioning
confidence: 99%
“…Buntungu et al reported a rudimentary horn pregnancy in a 6th gravida with all previous normal deliveries with a diagnosis of intrauterine fetal demise in this pregnancy where induction with misoprostol failed leading to the suspicion of ectopic pregnancy. 13 They placed a Foley catheter into the uterine cavity prior to performing a transabdominal ultrasound scan, which obviously is not a preferred method of diagnosing an extrauterine pregnancy, but it proved to be a useful and cheap way of excluding an intrauterine pregnancy. This method has been used by others also to confirm an extrauterine pregnancy which proved to be a rudimentary horn pregnancy at laparotomy.…”
Section: Gaur Y Et Al Int J Reprod Contracept Obstet Gynecol 2017 Smentioning
confidence: 99%